2007
DOI: 10.1016/j.bbr.2007.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age on the dynamics and the level of c-Fos activation in response to acute restraint in Lewis rats

Abstract: Recent studies have reported an age-related increase of anxiety in rodents with a concomitant decrease in neuronal activity in some of the key structures of the fear/anxiety circuit. In the present study we present evidence that distinct parts of this circuit are differentially affected by age in Lewis rats. The effect of ageing is observed both at the actual level of neuronal activation and its time-course. While the structures belonging to the HPA axis react with a bigger neuronal activation and almost no ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…The expression of c-Fos is commonly used as a marker for neuronal activity following a stimulus 25 . We stained the hippocampus for c-Fos under basal conditions or 90 min after stress, at the time of peak expression after stimulation 26 . In accordance to our previous results, the numbers of c-Fos-positive cells in the DG and CA3 after stress stimulation were significantly increased in WT, while no significant difference in CA1 was observed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of c-Fos is commonly used as a marker for neuronal activity following a stimulus 25 . We stained the hippocampus for c-Fos under basal conditions or 90 min after stress, at the time of peak expression after stimulation 26 . In accordance to our previous results, the numbers of c-Fos-positive cells in the DG and CA3 after stress stimulation were significantly increased in WT, while no significant difference in CA1 was observed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While the aging HPA axis is considered hyper-active (Meaney et al, 1992; Bizon et al, 2001; Herman et al, 2001; McEwen, 2008; Lupien et al, 2009), central components like excitatory amino acid level, corticotropin-releasing hormone, glucocorticoid receptor level, and CNS localized amplification of glucocorticoid action likely play a role (Lowy et al, 1995; Mabry et al, 1995; Herman et al, 2001; McEwen, 2001; Meyza et al, 2007; Yau and Seckl, 2012). As opposed to exaggerated glucocorticoid responses to non-psychosocial stressors (Sapolsky et al, 1986a) aged animals appear to have either the same or a blunted corticosterone or nerve growth factor response to psychosocial stressors like restraint (Stewart et al, 1988; Scaccianoce et al, 2000; Herman et al, 2001; Shoji and Mizoguchi, 2010; Garrido et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Including more time points after stress also may have been informative. For example, other studies have reported a secondary wave of Fos (Meyza et al, 2007) and of Zif268 (Day et al, 2001) expression in the amygdala 4 h after a stress exposure. Further, glucocorticoid receptor‐induced hippocampal zif268 expression has been shown to occur through the activation of both rapid‐onset and slow‐onset pathways (Revest et al, 2005).…”
Section: Discussionmentioning
confidence: 99%